OPTIMALISASI PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM MEMBERIKAN INFORMASI PUBLIK OLEH KECAMATAN BANJARSARI KABUPATEN CIAMIS - Fazar Ariangga; Otong Husni Taufiq; Neti Sunarti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the finding that the Optimization of Instagram Social Media Utilization in Providing Public Information by Banjarsari Subdistrict, Ciamis Regency has not run optimally due to limited internet coverage, limited human resources managing social media, the absence of dedicated staff fully responsible for information publication, as well as a lack of consistency in updating content. The research problem in this study is: How is the optimization of Instagram social media utilization in providing public information by Banjarsari Subdistrict, Ciamis Regency. The data sources in this research consist of 6 informants. This research uses a qualitative descriptive method. The data analysis techniques used in this study include data collection, data reduction, data presentation, and verification. The Research Results and Discussion show that the Optimization of Instagram Social Media Utilization in Providing Public Information by Banjarsari Subdistrict, Ciamis Regency has not been optimal. This is due to several obstacles, such as limited human resources, and the fact that posting information on Instagram is carried out by only one person. The content of the posts is also less attractive because there has not been any highly innovative development along with limited human resources. The community’s limited access to social media, especially for residents who do not own devices or are not active Instagram users, causes the conveyed messages to not reach all layers of society. There is low community participation in these activities, limited equipment and human resources capable of producing creative content with good quality, limited directed content planning, a lack of evaluation regarding the effectiveness of information dissemination, and minimal human resources who understand digital communication strategies. Overall, it has still not run optimally.